1990
DOI: 10.1111/j.1365-3059.1990.tb02509.x
|View full text |Cite
|
Sign up to set email alerts
|

Puccinia striiformis f.sp. tritici in Australasia: pathogenic changes during the first 10 years

Abstract: Pathogenic attributes of the wheat stripe rust pathogen were monitored in annual surveys from the first recording of this disease in Australia in 1979. During the 10‐year period to 1988,15 different pathotypes were detected in Australia and New Zealand. The pathotypes included some of economic importance to commercial wheat cultivars and others with no obvious selective advantage to aid their survival. Single‐gene mutations were the most likely causes of variation. The implications of these results on pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
137
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(139 citation statements)
references
References 10 publications
1
137
0
1
Order By: Relevance
“…The 'world-set' and the 'European set' each comprised eight differential lines (Stubbs, 1985). Moreover, Kema and Lange (1992) proposed incorporating Yr15 in the differential set of cultivars through extension of the 'world set', and a similar suggestion for Yr5 by Wellings & McIntosh (1990) was adopted here. In addition, Stubbs (1988) suggested Kalyansona (Yr2) and Federation *4/Kavkaz (Yr9) and Bariana and McIntosh (1994) proposed another differential cultivar, VPM1 (Yr17) to be included as supplemental differential sets for yellow rust.…”
Section: Differential Linesmentioning
confidence: 99%
“…The 'world-set' and the 'European set' each comprised eight differential lines (Stubbs, 1985). Moreover, Kema and Lange (1992) proposed incorporating Yr15 in the differential set of cultivars through extension of the 'world set', and a similar suggestion for Yr5 by Wellings & McIntosh (1990) was adopted here. In addition, Stubbs (1988) suggested Kalyansona (Yr2) and Federation *4/Kavkaz (Yr9) and Bariana and McIntosh (1994) proposed another differential cultivar, VPM1 (Yr17) to be included as supplemental differential sets for yellow rust.…”
Section: Differential Linesmentioning
confidence: 99%
“…Two types of resistance have been identified in several cereal-rust pathosystems: hypersensitive or qualitative (race specific) and quantitative (race-nonspecific) resistance. Race-specific resistance is highly effective but not durable because cultivars with such a type of resistance often become susceptible within a few years of release either as a consequence of selecting previously rare races or as a consequence of the development of new races (Wellings and McIntosh 1990;Line and Qayoum 1992;Chen 2005Chen , 2007. Conversely, race-nonspecific resistance is mainly polygenic and is known to be long-lasting and more durable (Herrera-Fossel et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The first response to the incursion, which caused heavy losses in some of the most widely grown varieties such as Zenith, was to deploy vertical resistance genes (YrA and Yr6). However, the effectiveness of these genes was lost very rapidly (Wellings & McIntosh, 1990). It was observed that some wheat varieties such as Condor, Egret and Olympic, although clearly susceptible at the seedling stage, showed varying degrees of adult-plant resistance and suffered much lower losses than the very susceptible varieties such as Zenith (McIntosh & Wellings, 1986).…”
Section: Resistance To Stem Rust and Stripe Rust In Wheatmentioning
confidence: 99%